How Fast Can Predictability Influence Word Skipping During Reading? - Fitzsimmons, Gemma; Drieghe, Denis (Journal of Experimental Psychology. Learning, Memory & Cognition, 2013)
Participants' eye movements were tracked when reading sentences in which target word predictability was manipulated to being unpredictable from the preceding context, predictable from the sentence preceding the one in which the target word was embedded, or predictable from the adjective directly preceding the target word. Results show that there was no difference in skipping rates between the 2 predictability conditions, which were skipped more often than the neutral condition. This suggests that predictability can impact the decision of whether to skip a word to a similar degree irrespective of whether the predictability originated from the prior word or the entire preceding sentence context. This finding can only be explained by models of eye-movement control during reading that assume that word ? is processed up to a high level before the decision to skip word ? + 1 is made.